Tangible benefits or token gestures: does Bwindi impenetrable National Park's long established multiple use programme benefit the poor? - Bitariho, Robert; Sheil, Douglas; Eilu, Gerald (Published by Taylor&Francis, 2015)
Trade and use of Non-timber forest products (NTFPs) has often been suggested as a means through which forest dependent people can improve their livelihoods to overcome poverty. Many projects have indeed promoted trade and use of NTFPs as a means of achieving development and conservation goals. One of the earliest large-scaleinitiatives to explore this was the Bwindi’s Multiple Use programme (MUP) in Southwest Uganda that began in 1994. The MUP allows limited park access by local people for medicine and basketry plants, and beekeeping. Here, we assess the development benefits obtained by local people through the MUP two decades after itsintroduction. Using data from 384 randomly sampled households and repeated marketsurveys over a 1-year period, we determined household preferences, dependency and incomes from NTFPs. The NTFPs that are most preferred by local people are those prohibited by park management. Furthermore, the highest income per household from NTFPs trade was estimated at 119 US $ per annum (14% of total household income).Restrictive policies on NTFPs extraction curtail tangible benefits to the local people.Restrictions ensure that NTFPs use cannot be increased, thus, despite their significant contribution to welfare, Bwindi’s NTFPs remain of negligible value for improving livelihoods.
Improving livelihood
Keywords: multiple use programme benefit; Tangible benefits or token gestures; Bwindi impenetrable National Park's